2018
DOI: 10.1103/physrevb.97.184518
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation in quantum turbulence in superfluid He4 above 1 K

Abstract: There are two commonly discussed forms of quantum turbulence in superfluid 4 He above 1K: in one there is a random tangle of quantizes vortex lines, existing in the presence of a non-turbulent normal fluid; in the second there is a coupled turbulent motion of the two fluids, often exhibiting quasi-classical characteristics on scales larger than the separation between the quantized vortex lines in the superfluid component. The decay of vortex line density, L, in the former case is often described by the equatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…This theory, as the modified Vinen equation, assumes (rather than infers) the existence of a diffusion process of vortex loops by postulating Brownian character of the vortex loops' dynamics. A superfluid's effective viscosity is also discussed in the different but related problem of the decay of superfluid turbulence, with experimental and numerical values [33][34][35][36] approximately in the range 0.01 < ν ′ /κ < 1 but more concentrated around 0.1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory, as the modified Vinen equation, assumes (rather than infers) the existence of a diffusion process of vortex loops by postulating Brownian character of the vortex loops' dynamics. A superfluid's effective viscosity is also discussed in the different but related problem of the decay of superfluid turbulence, with experimental and numerical values [33][34][35][36] approximately in the range 0.01 < ν ′ /κ < 1 but more concentrated around 0.1.…”
Section: Discussionmentioning
confidence: 99%
“…Physically, in this zero temperature limit, χ 2 models a sink of vortex lines due to dissipation of kinetic energy through both vortex reconnections and phonon emission (induced by high frequency Kelvin waves [25]). It has been noted that χ 2 depends on the local vortex line density at finite temperatures [36]. We independently estimate values of χ 2 in the zero-temperature limit, using the full Biot-Savart law of Eq.…”
Section: B Determining the Effective Diffusionmentioning
confidence: 99%
“…provided the counterflow velocity ρv n /ρ s exceeds a small critical velocity v 0 . To illustrate agreement with σ G1 , we computed v 2 L 1/2 using values for γ (a temperature-dependent parameter relating L to v ns ), v 0 , and the parameter c 2 reported in the recent work of Gao et al [27,28], and we approximated the mean vortex line spacing ℓ = L −1/2 across the entire parameter space. Since the agreement between σ G1 and v 2 L 1/2 appeared to be reasonable, we can use measured G1 velocity fluctuations to represent v 2 L 1/2 , and apply Eqn.…”
Section: Experimental Measurement Of Cmentioning
confidence: 99%
“…Since estimation of spatially-dependent c 2 is still beyond the capability of numerical simulations [28], and the traditional second sound method provides averaged information across the measurement volume, application of PTV to make whole-field measurements of G1 velocity fluctuations offers a unique opportunity to investigate the spatial dependence of c 2 .…”
Section: Experimental Measurement Of Cmentioning
confidence: 99%
“…Recent advances in the experimental techniques, including flow visualization [22][23][24] , as well as increasing computing power, renewed the interest to the spatial inhomogeneity due to presence of channel walls 19,[25][26][27][28][29][30][31] and spatially-resolved investigations of the transient behavior in the thermal counterflow 32 . The latter work showed that the vortex tangle that eventually fills the whole channel, grows starting from a number of remnant vortex rings.…”
Section: Introductionmentioning
confidence: 99%